Do Ethical Standards Matter? Evidence on Auditor Behavior and Audit Quality - Yohanes Sri Guntur; Maria Goretti Kentris Indarti; Pancawati Hardiningsih; Jacobus Widiatmoko (International Journal of Economics, Management and Accounting, 2026)
Financial reporting integrity is heavily reliant on audit quality. This research explores the effect of auditor attributes, specifically integrity and professional background, on audit standards in Timor-Leste. Quantitative data was collected from a survey of 60 auditors and analyzed using descriptive statistics, correlation analysis, and multiple linear regression techniques. The findings suggest that auditor ethics has a substantial positive impact on audit quality, indicating that conformity to professional ethical guidelines is vital for enhancing audit results. In contrast, experience in auditing does not demonstrate a statistically significant impact on the quality of audits. Visualization through scatter plots further supports the notion that the relationship between ethics and audit quality is more robust than that of other auditor characteristics. Strengthening ethical standards in the auditing profession is crucial to enhancing audit quality, as these findings demonstrate. This study contributes to the body of research on auditing behavior by presenting empirical findings from a developing institutional setting. The findings also have practical implications for policymakers and auditing bodies in Timor-Leste.